Analisis Rugi-rugi Macrobending pada Core Serat Optik Berstruktur Singlemode-Multimode-Singlemode - Sisca Arisya Harry Andhina (Jurnal Jaringan Telekomunikasi, 2019)
Macrobending often occurs in optical fibers that embedded in the ground due to shifting of soil or rocks in the ground causing interference in transmission. In this study used single-mode-multimode-singlemode fiber optic cable connected manually and axially measured using a light source test equipment and optical power meter and the results will be compared. The measurement results obtained the greater value of macrobending losses with the smaller the diameter of the winding, and the greater the number of turns. The highest value of macrobending losses in multimode cables is -1.48dB at 0.5cm diameter with 5 turns, highest value of macrobending losses on single mode cables is -12.73dB at 0.5cm diameter with 5 turns, lowest value of macrobending losses for multimode cables is -0.44dB at 5cm diameter with 1 twist, lowest macrobending losses in singlemode cables is -1.69dB at 5cm diameter with 1 twist. While the value of macrobending losses on axially connected SMS cables shows the highest value of macrobending losses on multimode cables is -1.12dB in diameter of 0.5cm with 5 turns, highest value of macrobending losses on singlemode cables is -1.18dB at diameter of 0.5cm with 5 turns, lowest value for macrobending losses on multimode cables is -0.66dB at 5cm in diameter with 1 twist, the smallest value for macrobending losses on singlemode cables is -0.27dB at 5cm diameter with 1 twist . The measurement results also showed that the macrobending losses of manually connected SMS cables were greater than the macrobending losses of axially connected SMS cables.